Dari Masa Lalu ke Masa Kini: Memori Kolektif, Konstruksi Negara dan Normalisasi Anti-Komunis - Hardiyanti Munsi (ETNOSIA : Jurnal Etnografi Indonesia, 2016)
AbstractThis article is focused on how the incident of G30S/PKI has left atrauma to the state and how the state deals with it in the era afterwards. It show that such incident is constructed by the state that PKI is the enemy of the state and threathens the sovereignity of the state ideology, and this is embedded to shape a collective memory. This has been used to construct and to normalize the anti-communist movement in Indonesia through various strategies by, for example, the establishment of Monumen Pancasila Sakti, the suppression of communist movement, the military recruitment, and a variety of doctrines in the military education. These aim to construct a united understanding about the incident of G30S/PKI and to normalize the anti-communist discourse in Indonesia. Keywords: Collective memory, PKI, G30S/PKI, TNI, state, construction, anti-communist,normalization